Hubungan Usia dan Paritas dengan Kejadian Ketuban Pecah Dini di Polindes Arus Deras Kalimantan Barat - Ass Two Diana Putri; Maryati Sutarno (Universitas Malahayati Lampung, 2025)
ABSTRACT There is still a high incidence of premature rupture of membranes in the Polindes of Aur Village, West Kalimantan. Of the cases that were most frequently encountered, among others, from 76 births, 20 were with PROM (16.1%), 8 were with a long second stage (6.4%) and 2 were with PEB (1.6%). To study the relationship between age and parity and the incidence of premature rupture of membranes in the Arus Deras Village Polindes, West Kalimantan in 2024. Analytical Survey, with a cross sectional approach, the population in this study were all mothers giving birth at the Polindes Community Health Center, Arus Deras Village, West Kalimantan from January to September 2024 as many as 76 people, with a total sampling technique with a sample size of 76 respondents, data collection with secondary data using a checklist sheet, univariate and bivariate analysis using chi square (Pearson chi square). From the results of univariate analysis of 76 respondents, 20 (26.3%) experienced premature rupture of membranes and 56 (73.7%) did not experience premature rupture of membranes. From the results of the chi square test, it is known that there is a relationship between age (ρ value = 0.000) and parity (ρ value = 0.000) with the incidence of premature rupture of membranes in the Arus Deras Village Polindes, West Kalimantan in 2024 with the value. Can provide input for midwives in screening for risk factors for premature rupture of membranes, so that by carrying out this screening the occurrence of premature rupture of membranes can be prevented. Keywords: Age, Parity, Premature, Rupture of Membranes ABSTRAK Masih tingginya angka kejadian ketuban pecah dini di Polindes Desa Aur Kalimantan barat. Dari kasus yang paling banyak ditemui antara lain dari 76 persalinan sebanyak 20 persalinan dengan KPD (16.1%), 8 persalinan dengan kala II lama (6.4%) dan 2 persalinan dengan PEB (1.6%). Untuk mempelajari Hubungan antara Usia dan Paritas dengan Kejadian Ketuban Pecah Dini di Polindes Desa Arus Deras Kalimantan Barat Tahun 2024. Survei Analitik, dengan pendekatan secara cross sectional, populasi dalam penelitian ini seluruh ibu bersalin di Polindes Desa Arus Deras Kalimantan Barat dari bulan Januari s/d September 2024 sebanyak 76 orang, dengan teknik total samplling dengan jumlah sample 76 responden, pengumpulan data dengan data sekunder menggunakan lembar cheklist, analisis univariat dan bivariat menggunakan chi square (pearson chi square). Dari hasil analisis univariat dari 76 responden sebanyak 20 (26,3%) mengalami Ketuban Pecah Dini dan sebanyak 56 (73.7%) tidak mengalami Ketuban Pecah Dini. Dari hasil uji chi square diketahui bahwa ada hubungan usia (ρ value = 0,000) dan paritas (ρ value = 0,000) dengan kejadian Ketuban Pecah Dini di Polindes Desa Arus Deras Kalimantan Barat Tahun 2024 dengan nilai. Dapat memberikan masukkan bagi bidan dalam melakukan skrining faktor risiko terjadinya ketuban pecah dini, sehingga dengan melakukan skrining tersebut kejdaian ketuban pecah dini dapat dicegah. Kata Kunci: Usia, Paritas, Kejadian, Ketuban Pecah Dini